Temporal and Spatial Categorization in Human and Non-Human Primates - Mendez, Juan Carlos; Prado, Luis; Mendoza, German; Merchant, Hugo (Frontiers in Integrative Neuroscience, 2011)
It has been proposed that a functional overlap exists in the brain for temporal and spatial information processing. To test this, we designed two relative categorization tasks in which human subjects and a Rhesus monkey had to assign time intervals or distances to a ‘short’ or ‘long’ category according to varying prototypes. The performance of both species was analyzed using psychometric techniques that showed that they may have similar perceptual, memory and/or decision mechanisms, specially for the estimation of time intervals. We also did a correlation analysis with human subjects’ psychometric thresholds and the results imply that indeed, temporal and spatial information categorization share neural substrates. However, not all of the tested distances and intervals correlated with each other, suggesting the existence of sub-circuits that process restricted ranges of distances and intervals. A different analysis was done on the monkey data, in which the influence of the previous categorical prototypes was measured on the task currently being performed. Again, we found a significant interaction between previous and current interval and distance categorization. Overall, the present paper points towards common or at least partially overlapped neural circuits for temporal and spatial categorization in primates.